PENGARUH SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR DI ACEH BARAT) - Rossa Rossa; Evayani Evayani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The research examines the influence of the accounting information systems and internal controls on the company performance. The population in this research is all palm oil companies registered at the Badan Pusat Statistik (BPS) of Aceh Barat.  The sampling technique used is saturation sampling. This research uses primary data which obtained through the questionnire results. The data were collected 68 questioners from 3 palm oil companies. Data were processed using SPSS version 22 and analyzed using multiple linear regression, The results show that (1) accounting information systems and internal controls simultaneously, significantly affecting company performance (2) accounting information systems has a positive and significant effect on company performance (3) internal control has a positive and significant effect on company performance